PERILAKU MENYIMPANG DI DUNIA PENDIDIKAN (Studi kasus Evaluasi pembelajaran di MA NW Dames) - AHMAD ARDABILLI (Universitas Hamzanwadi, 2020)
Deviant behavior is a form of behavior or action that is not in accordance with the norms in the community. While deviant behavior in education Dimiyati (1980: 32) stated that the deviant behavior of children / adolescents in terms of education is that they are considered to interfere with the process of teaching and learning in school, do not obey the rules that have difficulties in association and other aspects that interfere and harm themselves or harm others. As a result, all of these behavioral irregularities were repeated repeatedly by them. The method in this study is a qualitative research method with a descriptive approach. The type of research used in this study is a case study (case study) From the studies conducted, this study resulted in deviant behavior in the world of education that often occurs during evaluation of learning. In the process of evaluating learning deviations carried out by students that is working together in working on exam questions (cheating).